Evolution of Passive Film on 304 Stainless Steel During Nitric Acid Passivation. Issue 8 (5th May 2022) - Yue, Yingying; Liu, Chengjun; Jiang, Maofa
Abstract : The corrosion resistance of 304 stainless steel is dominated by the passive film on its surface. The main purpose of the present study is to validate the critical factor determining the corrosion resistance of the passive film and identify the optimized passivating time in nitric acid under chemical oxidation. The electrochemical results show that the passive film consists of an outer layer behaving as a p ‐type semiconductor and an inner layer behaving as an n‐type semiconductor. The film thickness and film resistance increase to maximum values after 2.67 h with the lowest carrier densities. Afterward, the properties of the passive film reach a steady state with higher carrier densities. The X‐Ray photoelectron spectroscopy results indicate that the gradual dissolution of FeOOH and further oxidation of Fe 2+ species in nitric acid contribute to the decrease of corrosion resistance of the passive film. The thickness of the passive film is accurately predicted according to electrochemical impedance spectroscopy data based on the Hsu‐Mansfeld (H–S) model. Abstract : The dynamic growth and evolution of passive film on stainless steel under chemical oxidation in nitric acid are thoroughly investigated, and the evolution mechanism of passive film is proposed on the base of the point defect model. The major factor in the deterioration of passive film is determined, and the desired passivation duration is obtained.